ANALISA PENGARUH AIR LAUT TERHADAP KETAHANAN MESIN KAPAL PADA KAPAL NELAYAN SEBAGAI AIR PENDINGIN - Triadi Prasetyo Anggara; Yulia Ayu Nastiti; Sofianna Agustin (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2023)
The cooling system is a system that functions to maintain the engine temperature at a certain temperature in accordance with the specified design so that the diesel engine can operate continuously. For cooling of a diesel eninge. Fisherman Village of Ngimbo Village is a coastal area which is an area full of marine potential, the local community on average works as fisherman. This research was conducted using the interview method with fisherman, especially those who own boats. The questionnaire was addressed to 10 fisherman. The results of the study show that fisherman’s boats in Ngimbo Village use seawater cooling, in wich fisherman modify the cooling system of the Dongfeng brand diesel engine using a head exchanger for fishing motor boats aiming for cooling water temperatures in the 60°C - 90°C range and replacing the open cooling system method which are considered less efficient and have many negative impacts on the engine such as corrision and the temperature of the cooling water in the water jacket is brought to the specified standard. Special orecautions must be taken to accommodate open systems. For example, some engines can be equipped with an aftercooler as well as cleaning the core of the corrosion-resistant pipe. Aftercoolers from round tubes are designed lik fin plates and can be disassembled for cleaning, so they are ready for use in open systems.